Causas y frecuencia de cesárea en el Centro Materno Infantil Municipal Julia Esther González Delgado durante el año 2015. - Fernández Huaca, Cristina Carlota (2017)
The present research paper called causes and frequency of cesarean section in the municipal maternal childhood municipal julia esther gonzalez delgado during the year 2015.The general objective is to determine the prevalence and causes associated with the accomplishment of caesarean sections in the maternal center during the year 2015 , while the specific objectives are to determine the prevalence and to stratify by age group, establishing the most frequent gestational age, by which the patients underwent cesarean section and identify the main causes of cesarean : maternal ,fetal ,maternal-fetal and obstetric . This is a descriptive and retrospective study with a quantitative approach. In the universe was 217 patients, during the year 2015 of which 200 clinical histories meet the inclusion criteria. As for the results, a prevalence of 92.17% was obtained, the age group with the highest percentaje was 44.50% between 16-23 years of age and the maternal factors represented the main causes for cesarean section with 43.02%, followed of Obstetric factors with 28.2%. The main indication for this intervention is the previous cesarean section with 40%, cephalopelvic disproportion 23.5%, presentation dystocia 6%,It was demonstrated that the cesarean rate exceeds what is recommended by OMS and among the main causes are the maternal, followed by obstetric ones; the previous cesarean section is the main indication of cesarean delivery, followed by cephalopelvic disproportion, the age group in which this intervention was performed more frequently was between 16-23 years and the most frequent gestational age was 37-41 weeks.. KEYWORDS: Caesarean section, Maternal causes, fetal, obstetric.